Molecular Characterization of a New Moniliformis sp. From a Plateau Zokor (Eospalax fontanierii baileyi) in China - Dai, Guo-Dong; Yan, Hong-Bin; Li, Li; Zhang, Lin-Sheng; Liu, Zhan-Long; Gao, Sheng-Zhi; Ohiolei, John Asekhaen; Wu, Yao-Dong; Guo, Ai-Min; Fu, Bao-Quan; Jia, Wan-Zhong (Frontiers in Microbiology, 2022)
In the present study, a new species of the genus Moniliformis species is described taxonomically in the mitochondrial genomic context. The parasite was found in a plateau zokor captured in a high-altitude area of Xiahe County of Gansu Province, China. The mitochondrial (mt) genome length of this new species was 14066 bp comprising 36 genes and 2 additional non-coding regions (SNR and LNR), without atp8. The molecular phylogeny inferred by the cytochrome c oxidase subunit I gene (cox1) and the18S ribosomal RNA gene (18S rDNA) sequences showed that the parasite as a sister species to other Moniliformis spp. and was named Moniliformis sp. XH-2020. The phylogeny of the concatenated amino acid sequences of the 12 protein-coding genes (PCGs) showed Moniliformis sp. XH-2020 in the same cluster as Macracanthorhynchus hirudinaceus and Oncicola luehei confirming the cox1 and 18S rDNA phylogenetic inference. In addition, the entire mt genome sequenced in this study represents the first in the order Moniliformida, providing molecular material for further study of the phylogeny of the class Archiacanthocephala. Moreover, the species of this class, use arthropods as intermediate hosts and mammals as definitive hosts and are agents of acanthocephaliasis, a zoonosis in humans. Therefore, this study not only expands the host range among potential wild animal hosts for Archiacanthocephalans which is of great ecological and evolutionary significance but also has important significance for the research of zoonotic parasitic diseases.